Emotional Intelligence in Distance Learning: A Case Study of English as a Second Language via Distance Learning - George Boon Sai Teoh; Agnes Wei Lin Liau (National Research University Higher School of Economics, 2021)
Distance learners studying English confront emotionally demanding obstacles. A mixed methods study was conducted to explore the role that distance learners' emotional intelligence (EI) plays as they learn English. In phase one of the study, 238 students responded to a composite questionnaire that yielded their EI scores, demography, and viewpoints regarding the English course. In phase two, 18 volunteers selected based on their EI scores were interviewed to obtain qualitative data to build upon the quantitative results. This paper presents a case study of a student called Aini. The findings revealed that Aini's EI helped her manage her emotions, perceptions, and actions, and ultimately obtain her obligatory English credits for graduation. It is imperative to inculcate students' EI to help them manage their emotions in order to adapt and persevere, not only when learning English via distance learning but also to successfully accomplish one's goals in life.